Testosterone-treated cows to aid in heat detection - Laaser, G.N.; Kiracofe, G.H. (Kansas State University. Agricultural Experiment Station, 2011)
Eight cull Hereford cows were given 200-mg. injections of testosterone proprionate repository (Haver-Lockhart, Shawnee, KS) every other day for 20 days (10 injections). Four cows were given weekly booster injections with the same testosterone proprionate; the other four were injected every three weeks with testosterone enanthate (sigma Chemical Co., St. Lois, MO.). Each cow was equipped with a chin-ball marker and each was used to detect heat in other cows. The detection period lasted approximately 45 days. Testosterone-treated cows served satisfactorily as heat detectors; those given boosters of testosterone proprionate marked more cows in heat than those given testosterone enanthate.
What's Ahead for Cattlemen? is known as Cattlemen’s Day, 1977
Keywords: Beef; Testosterone; Heat detection